PERSEPSI MAHASISWA TERHADAP TINGKAT KESULITAN MATA KULIAH KALKULUS: KAJIAN LITERATUR TENTANG FAKTOR PENYEBAB DAN STRATEGI PEMBELAJARAN - Maharani, Salsabilla; Tussyauni, Annisa; Adrian, Rifki Rio; Putra, Rehan Dwi; Riendaffa, Farhan; Afgani, M Win (Universitas Batanghari Jambi, 2026)
Calculus is a fundamental subject that plays an important role in various scientific disciplines, yet it is often perceived as difficult by university students. This study aims to examine students’ perceptions of the difficulty of calculus, identify the contributing factors, and explore effective learning strategies to address these challenges. The research employs a library research method by analyzing relevant scientific literature. The results indicate that calculus is still considered difficult by most students due to internal factors such as low prior knowledge, weak conceptual understanding, low motivation, and negative attitudes, as well as external factors including the abstract nature of the material and less varied teaching strategies. Students’ difficulties are reflected in errors in understanding concepts, recalling formulas, and performing calculations. To overcome these issues, student-centered learning strategies are required, including strengthening basic concepts, intensive practice, the use of interactive media, project-based learning, and group discussions. With appropriate strategies and a supportive learning environment, negative perceptions of calculus can be reduced, leading to improved student understanding